Functional management of intellectual property of industrial enterprises: organizational and methodological aspect - Cherepanova, V. O.; Sylka, I. V. (My University, 2021)
The article deals with the organization of functional management of intellectual property of industrial enterprises, since under conditions of insufficient funding of activities intangible assets can increase the market value of an enterprise, improve its financial condition and image. A comparative analysis of the use of intangible assets of Ukrainian, European and US companies has been held. It has been established that Ukrainian enterprises use only one intangible asset, i.e. software rights, which does not encourage the use of these assets. The article proposes a methodological approach to the organization and implementation of intellectual property functional management, allowing: to join enterprises using goodwill and geological information; to sell fuel and energy resources of own production facilities based on the certificate of origin; environmental permits, which set the maximum allowable concentrations of pollutants; operating permits for the production and maintenance of imported coal.
Keywords: intellectual property; management functions; functional management; goodwill; certificate; environmental permits; operating permits